2018
DOI: 10.1177/1460458218792688
|View full text |Cite
|
Sign up to set email alerts
|

Design and acceptability of a psychosocial text messaging intervention for victims of gender-based violence

Abstract: Mobile phones can produce detailed and personalized data to help diagnose, treat, prevent or rehabilitate women who are victims of gender violence. We sent automatic text messages, based on cognitive-behavioural therapy, to female victims of gender violence to assess the feasibility of the medium for mental health intervention. During the 28-day intervention period, each woman received four automatic text messages every day on a pre-established schedule. We evaluated symptoms of depression using the Personal H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Previous research has shown that text messaging contributes to the effectiveness of face-to-face therapy, improves care, and allows users to be counseled more intensively and frequently by avoiding trips to face-to-face consultations to meet the therapist (Aguilera 2015;Agyapong et al 2016;Campbell et al 2015;Hall et al 2015;Kong et al 2014;García et al 2018;Stevens et al 2019). However, these past studies did not differentiate between therapies using specific text messages for men and women; those for highly vulnerable people, such as immigrant women; or by the degree of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that text messaging contributes to the effectiveness of face-to-face therapy, improves care, and allows users to be counseled more intensively and frequently by avoiding trips to face-to-face consultations to meet the therapist (Aguilera 2015;Agyapong et al 2016;Campbell et al 2015;Hall et al 2015;Kong et al 2014;García et al 2018;Stevens et al 2019). However, these past studies did not differentiate between therapies using specific text messages for men and women; those for highly vulnerable people, such as immigrant women; or by the degree of depression.…”
Section: Discussionmentioning
confidence: 99%
“…La expansión de las TICs va más allá del ocio y uso personal, siendo estas empleadas también para el desarrollo de la labor profesional y no sólo en actividades laborales relacionadas con la ingeniería o tecnología. Existen ejemplos de cómo profesionales de la psicología en España y otros lugares del mundo están comenzando a hacer uso de estas herramientas para desarrollar su labor en distintos campos de esta disciplina como en la educación (Mera et al, 2019), promoción de la salud (Seiler et al, 2017), prevención del estigma (Mullor et al, 2019), neuropsicología (Irazoki et al, 2020) e intervención en servicios sociales (García et al, 2019).…”
Section: Introductionunclassified